SALT EFFECTS IN THE KINETICS OF REACTION BETWEEN IODIDE AND BROMATE IONS (Biological Sciences - PJSIR, 2002)
A bimolecular reaction between potassium iodide and potassium bromate in presence of sodium  nitrate  was studied  at  various ionic strengths (µ) and temperatures. The results showed that the rate constants  (k) increased with  the increase in  ionic strength of the medium. The values  of energy  of activation  (E) and activation  parameters  such as change in enthalpy  of activation (Af-I#), change in entropy of activation (1".S#) and change in free energy of activation (l".QII) were evaluated as  a  function  of ionic  strength  of the medium.